2005
DOI: 10.1111/j.1747-4477.2005.tb00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Of Invasive Cervical Resorption With MTA: Case Report

Abstract: This paper presents a case report of a maxillary lateral incisor affected by invasive cervical resorption. The tooth was submitted to a 21-day treatment with calcium hydroxide followed by root canal filling. The area of resorption was sealed with MTA followed by glass ionomer cement and restored with composite resin. Two-year radiographic follow-up showed stability of the resorption site and normal coronal colour and depth of gingival sulcus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 9 publications
1
12
0
1
Order By: Relevance
“…Several case reports have described successful treatment of external root resorption by using MTA to repair these defects. The authors have used surgical, nonsurgical, or a combination of these approaches for treatment of teeth with external resorption defects (126,(179)(180)(181)(182)(183)(184).…”
Section: Resorptionmentioning
confidence: 99%
“…Several case reports have described successful treatment of external root resorption by using MTA to repair these defects. The authors have used surgical, nonsurgical, or a combination of these approaches for treatment of teeth with external resorption defects (126,(179)(180)(181)(182)(183)(184).…”
Section: Resorptionmentioning
confidence: 99%
“…1993, Pitt Ford et al. 1995), for the repair of cervical resumption (Baratto‐Filho et al. 2005), as a pulp capping agent (Pitt Ford et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous studies have shown that MTA can be suitable for a wide variety of applications (12). Moreover, MTA has been used successfully to treat invasive cervical resorptions (13,14). One of the important properties of MTA is its superior ability to resist leakage (15), which may be explained by its superior marginal adaptation (16).…”
Section: Introductionmentioning
confidence: 99%